Results of Epizootiological Survey of the Mongolian Part of Trans-Baikal Steppe Natural Plague Focus in 2017 - S. V. Balakhonov; M. B. Sharakshanov; E. A. Vershinin; I. M. Makhinova; N. G. Revenskaya; A. B. Moshkin; S. A. Kosilko; B. Byambazhav; Ts. Gankhuyag; L. Erdenechimeg; Ts. Uuganbayar; Ch. Erdenechimeg; et al. (Проблемы особо опасных инфекций, 2017)
Objective of the study is to obtain the data on the state of Severokerulensky plague focus in Mongolia, adjacent to the Trans-Baikal steppe focus in the south. A reconnaissance investigation on plague in the territory of Dornod aimak was carried out by efforts of the joint Russian-Mongolian group of specialists. Material samples were tested under extended scheme using bacteriological, biological, serological, and molecular-genetic methods. Negative test results on plague allow for reporting the absence of risks of intensive and extensive epizooty development and agent importation into the territory of Russia. Though it is necessary to continue the survey in the territory of Khentii aimak, where the presence of active plague foci is registered.